DOES ENVIRONMENTAL CULTURE AND INTELLECTUAL CAPITAL ENHANCE FIRM VALUE AMID POLITICAL INFLUENCE? - Burhanuddin, Burhanuddin; Alfurkaniati, Alfurkaniati; Saputra, Dian; Arifin, Zidan Dwinanda; Pangestu, Galih Agestri (JRAK, 2025)
Corporate sustainability has been a key concern for investors and stakeholders, particularly in the Consumer Non-Cyclical (CNC) sector. Previous studies suggested that Environmental Organizational Culture (EOC) and Intellectual Capital (IC) could enhance firm value, but their impact remained debated. This study examined the effect of EOC and IC on firm value, with Political Connections (PC) as a moderating variable. Using panel data regression analysis on financial and sustainability reports from 2021–2022, the findings revealed that EOC and IC had a significant negative relationship with firm value. Additionally, PC moderated the relationship between EOC and firm value but did not significantly affect the IC-firm value relationship. These results suggested that investments in sustainability and intellectual capital might burden firms in the short term, whereas political connections favored tangible operational investments. This study provided insights for stakeholders in balancing sustainability strategies, intellectual capital, and firm value.